Care and nutrition: concepts and measurement - Engle, Patrice L.; Menon, Purnima; Haddad, Lawrence James (International Food Policy Research Institute, 1997)
Care is the provision in the household and the community of time, attention and support to meet the physical, mental, and social needs of the growing child and other household members. The significance of care has been best articulated in the UNICEF framework. This paper extends the model presented by UNICEF by defining resources for care and specific care behaviors, and presenting an argument for the importance of child characteristics in determining the level of care received. Resources for care are defined as caregiver education, knowledge and beliefs, caregiver physical health and nutritional status, caregiver mental health and self-confidence, autonomy and control of resources, workload and time availability, and family and community social support. Care behaviors discussed here are two of the six proposed: feeding and psychosocial care. This paper also proposes an orientation to the measurement of care, and provides suggestions for indicators for care resources and the two care behaviors, based on a summary of recent literature. Finally, the paper argues for greater attention to research on the causal linkages between care and child nutrition.